Cancer sensor - Mohd Isa, Maryam; Saripan, M. Iqbal; Wan Hasan, Wan Zuha; Ahadi, Mojtaba (Universiti Putra Malaysia Press, 2016)
Brain is part of the central nervous system (CNS) and it can be affected by cancer or cancer treatment. Pain from a tumour pressing on the nerves and cancer treatment can cause damage to the nerves. The number one leading cause of death among cancer in women is breast cancer. Besides affecting the nervous system, breast cancer patients also have a high tendency to develop brain metastases.